Interventions to improve physical activity during pregnancy: a systematic review on issues of internal and external validity using the RE‐AIM framework. (30th August 2016) - Craike, M; Hill, B; Gaskin, CJ; Skouteris, H
Abstract : Background: Physical activity (PA) during pregnancy has significant health benefits for the mother and her child; however, many women reduce their activity levels during pregnancy and most are not sufficiently active. Given the important health benefits of PA during pregnancy, evidence that supports research translation is vital. Objectives: To determine the extent to which physical activity interventions for pregnant women report on internal and external validity factors using the RE‐AIM framework (reach, efficacy/effectiveness, adoption, implementation, and maintenance). Search strategy: Ten databases were searched up to 1 June 2015. Eligible published papers and unpublished/grey literature were identified using relevant search terms. Selection criteria: Studies had to report on physical activity interventions during pregnancy, including measures of physical activity during pregnancy at baseline and at least one point post‐intervention. Randomised controlled trials and quasi‐experimental studies that had a comparator group were included. Data collection and analysis: Reporting of RE‐AIM dimensions were summarised and synthesised across studies. Main results: The reach (72.1%) and efficacy/effectiveness (71.8%) dimensions were commonly reported; however, the implementation (28.9%) and adoption (23.2%) dimensions were less commonly reported and no studies reported on maintenance. Conclusions: This review highlights the under‐reporting of issues of contextual factors in studies of physical activity during pregnancy. The translation of physical activity interventions during pregnancy could be improved through reporting of representativeness of participants, clearer reporting of outcomes, more detail on the setting and staff who deliver interventions, costing of interventions and the inclusion of process evaluations and qualitative data. Tweetable abstract: The systematic review highlights the under‐reporting of contextual factors in studies of physical activity during pregnancy. Tweetable abstract: The systematic review highlights the under‐reporting of contextual factors in studies of physical activity during pregnancy.